In Vitro and In Vivo Characterization of a Typical and a High Pathogenic Bovine Viral Diarrhea Virus Type II Strains - Malacari, Dario Amilcar; Pécora, Andrea; Pérez Aguirreburualde, Maria Sol; Cardoso, Nancy Patricia; Odeón, Anselmo Carlos; Capozzo, Alejandra Victoria (Frontiers in Veterinary Science, 2018)
Non-cytopathic (ncp) type 2 bovine viral diarrhea virus (BVDV-2) is widely prevalent in Argentina causing high mortality rates in cattle herds. In this study, we characterized an Argentinean ncp BVDV-2 field isolate (98-124) compared to a high-virulence reference strain (NY-93), using in silico analysis, in vitro assays, and in vivo infections of colostrum deprived calves to compare pathogenic characters and virulence. In vitro infection of bovine peripheral blood mononuclear cells (PBMC) with BVDV 98-124 induced necrosis shortly after infection while NY-93 strain increased the apoptotic rate in infected cells. Experimental infection of colostrum-deprived calves (CDC, n=4 each) with these strains caused an enteric syndrome. High pyrexia was detected in both groups. Viremia and shedding were more prolonged in the CDC infected with the NY-93 strain. Additionally, NY-93 infection elicited a severe lymphopenia that lasted for 14 days, whereas 98-124 strain reduced the leucocyte counts for 5 days. All infected animals had a diminished lymphoproliferation activity in response to a mitogen. Neutralizing and anti-NS3 antibodies were detected 3 weeks after infection in all infected calves. Virulence was associated with a more severe clinical score, prolonged immune-suppression and a greater window for transmission. Studies of apoptosis/necrosis performed after in vitro PBMC infection also revealed differences between both strains that might be correlated to the in vivo pathogenesis. Our results identified 98-124 as a low virulence strain.